El aprendizaje cooperativo en las escuelas interculturales bilingües. Estudio de caso del CECIB “General Alfonso Jaramillo”, de la comunidad de pucará desaguadero, cantón Otavalo, provincia de Imbabura. - Bedón Castro, Zaida (2014)
This paper addresses the issue of cooperative learning from the educational experience of those who make the Bilingual Intercultural Community Education Center "Gral Alfonso Jaramillo ". All Ecuadorian educational system has entered a process of renovation, the latest legal and curricular reforms invite a renewal of educational fact therefore no teacher, student or parent can be placed outside this process. Throughout the present work is an analysis regarding the use of the group as a learning and personal and social growth of those who come to this school, addresses some topics among which are the theoretical basis of cooperative learning and impact on the cognitive development of students, as the proposed center study is part of the IBE scheme, we review the same and compatibility don this learning strategy.